2006
DOI: 10.1038/sj.jp.7211496
|View full text |Cite
|
Sign up to set email alerts
|

A blinded, randomized, multicenter study of an intravenous Staphylococcus aureus immune globulin

Abstract: Objectives: Very low birth weight (VLBW) infants are vulnerable to nosocomial infections and subsequent morbidity; including infections caused by Staphylococcus aureus: 85% of nosocomial S. aureus infections are caused by capsular polysaccharide (CPS) types 5 and 8. Altastapht is a polyclonal investigational human immunoglobulin G (IgG) with high levels of opsonizing S. aureus CPS types 5 and 8 IgG.Methods: A Phase 2 clinical trial to assess the safety and kinetics of Altastaph in VLBW infants. Neonates in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 16 publications
0
51
0
Order By: Relevance
“…10 IVIg preparations aimed at reducing the incidence of infection with specific pathogens 66 seem to be safe in the study populations tested, 67 but larger studies have not shown efficacy. 68,69 At present, the available data are incomplete or do not support the suggested immunoenhancements attributed to IVIg in very premature neonates. Evaluation of IVIg-mediated effects on immune function should be performed using homogenous (exclusively very premature immune components) ex vivo and in vitro systems.…”
Section: Discussionmentioning
confidence: 76%
“…10 IVIg preparations aimed at reducing the incidence of infection with specific pathogens 66 seem to be safe in the study populations tested, 67 but larger studies have not shown efficacy. 68,69 At present, the available data are incomplete or do not support the suggested immunoenhancements attributed to IVIg in very premature neonates. Evaluation of IVIg-mediated effects on immune function should be performed using homogenous (exclusively very premature immune components) ex vivo and in vitro systems.…”
Section: Discussionmentioning
confidence: 76%
“…In a phase 2 study, low-birth-weight neonates were given two intravenous (IV) doses of AltaStaph or placebo. 18 The rates of adverse events between the two arms of the study were similar, and the rates of S. aureus bacteremia were nearly identical (»3%) in both groups. Another phase 2 trial enrolled patients with documented S. aureus bacteremia who received standard therapy plus Altastaph or placebo, 19 but the vaccineinduced CP antibodies were insufficient to significantly reduce S. aureus bacteremia in this at-risk population.…”
Section: Introductionmentioning
confidence: 61%
“…Similar obstacles have been encountered with attempts to use hepatocytes for in vitro drug toxicology assays and to model human liver diseases (3,4). Human embryonic and fetal stem cells can be propagated for extended periods in culture and can be differentiated to hepatocyte-like cells that are able to survive in vivo (5)(6)(7)(8). However, the ethical issues associated with their use and their limited availability have reduced enthusiasm for this approach.…”
Section: Toward a Better Understanding Of Antibody Immunity To S Aureusmentioning
confidence: 99%
“…Clinical trials with an investigational CP5-and CP8-based conjugate vaccine for S. aureus (StaphVAX) have been notable for largely negative results, in that the vaccine did not induce sustained protection against the development of disease (5,6). In addition, phase II trials with CP-specific immunoglobulin did not demonstrate an adjunctive therapeutic effect in adults (7) or prevent bacteremia in neonates (8). Although a vaccine for strains that do not express CP8 or CP5 (PentaStaph) is in clinical trials, disappointing results with existing investigational CP-based vaccines and immunotherapy highlight the fact that the mechanisms behind their lack of efficacy against S. aureus-associated disease are vexing and mysterious.…”
Section: Harnessing the Potential Of Cp As A Vaccine Target For S Aumentioning
confidence: 99%